2015
DOI: 10.2337/db15-1024
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ERK1/2 Ameliorates Liver Steatosis in Leptin Receptor–Deficient (db/db) Mice via Stimulating ATG7-Dependent Autophagy

Abstract: Although numerous functions of extracellular signalregulated kinase 1/2 (ERK1/2) are identified, a direct effect of ERK1/2 on liver steatosis has not been reported. Here, we show that ERK1/2 activity is compromised in livers of leptin receptor-deficient (db/db) mice. Adenovirusmediated activation of mitogen-activated protein kinase kinase 1 (MEK1), the upstream regulator of ERK1/2, significantly ameliorated liver steatosis in db/db mice, increased expression of genes related to fatty acid b-oxidation and trigl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 52 publications
0
37
0
Order By: Relevance
“…In the present study, we found that miR-30c-5p was significantly decreased in liver of leptin receptor deficient (db/db) mice, a classic animal model for liver steatosis [5]. And strikingly, exogenous miR-30c-5p delivered by recombinant adeno-associated virus (rAAV) markedly ameliorated abnormal triglyceride accumulation and liver steatosis in db/db mice, suggesting a new therapeutic strategy against NAFLD.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In the present study, we found that miR-30c-5p was significantly decreased in liver of leptin receptor deficient (db/db) mice, a classic animal model for liver steatosis [5]. And strikingly, exogenous miR-30c-5p delivered by recombinant adeno-associated virus (rAAV) markedly ameliorated abnormal triglyceride accumulation and liver steatosis in db/db mice, suggesting a new therapeutic strategy against NAFLD.…”
Section: Introductionmentioning
confidence: 82%
“…NAFLD is composed of a series of pathological changes in liver: 1) The initial stage is hepatic steatosis, characterized by the excess deposition of triglyceride and/or cholesterol in liver; 2) Abnormal hepatic lipid accumulation results from augmented de novo lipogenesis, and/or decreased β-oxidation; 3) If uncontrolled, hepatic steatosis can progress to cirrhosis, end-stage liver failure and hepatocellular carcinoma [4, 5]. Currently, no drug is licensed for the treatment of NAFLD [3, 6], and thus it is important to understand the mechanisms underlying NAFLD and develop new intervention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical Analysis-Hepatic and cellular lipids were extracted with chloroform/methanol (2:1), as described previously (51,52). TG, TC, FFAs, ALT, and AST were determined using a TG kit (BHKT Clinical Reagents, Beijing, China), a TC kit (SSUF-C, Shanghai, China), an FFA kit (Wako Pure Chemical Industries, Osaka, Japan), and an AST or ALT kit (ShenSuoYouFu, Shanghai, China), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Although some studies showed the lipogenic role of autophagy, most experiments supported autophagy as a lipolytic mechanism (6). Reduced autophagic function promotes the initial development of hepatic steatosis and progression of steatosis to liver injury, and agents to augment hepatic autophagy may have therapeutic potential in nonalcoholic steatohepatitis (8)(9)(10).…”
mentioning
confidence: 99%